PEMANFAATAN DAGING DAN TULANG IKAN KEMBUNG (Rastrelliger kanagurta) DALAM PEMBUATAN CAMILAN STIK - Siswanti, Siswanti; Agnesia, Priscilla Yolanda; Katri A, R. Baskara (Jurnal Teknologi Hasil Pertanian, 2017)
Snack stick is food in the form of thin slices and long flat-shaped that made of wheat flour, tapioca, fat, eggs, and water and then fried with oil and have a savory flavor and crunchy texture. The addition of fish in snack sticks product intended to increase the nutritional value of the snacks. Mackerel (Rastrelliger kanagurta) was chosen because it has a good nutrient for the body, one of them protein and calcium, it taste good and tasty, and the price are cheap. This study aim to determine the acceptance of panelist on sensory characteristics (color, aroma, flavor, texture and overall) snack stick with materials variation of mackerel and determine the influence of material variation mackerel to the chemical characteristic (moisture, ash, fat, protein, carbohydrate and calcium). The experimental design used was Completely Randomized Design (CDR) consisting of one factor material variation of mackerel. Stick used material variation of meat, bones, and whole mackerel. The results showed that the used of whole mackerel stick sensory (color, taste, and overall) aspect preffered by most panelist. Fish meat stick favored in texture and bones stick frowned upon in the aspects of the aroma. For the chemical characteristic of the fish meat stick has a value of moisture, ash, fat, protein, carbohydrates and calcium are 2.80%; 2.48%; 28.16%; 12.30%; 54.30%; and 0.03%. A fishbone stick in a row of 2.60%; 5.52%; 36.11%; 8.52%; 47.23%; and 0.68%. A whole  fish stick are 2.72%; 3.07%; 31.24%; 9.88%; 53.09%; and 0.15%.